“Is There An App For That?” Orthopaedic Patient Preferences For A Smartphone Application - Dattilo, Jonathan R.; Gittings, Daniel J.; Sloan, Matthew; Hardaker, William M.; Deasey, Matthew J.; Sheth, Neil P. (Applied Clinical Informatics, 2017)
Background: Patients are seeking out medical information on the Internet and utilizing smartphone health applications (“apps”). Smartphone use has exponentially increased among orthopaedic surgeons and patients. Despite this increase, patients are rarely directed to specific apps by physicians. No study exists querying patient preferences for a patient-centered, orthopaedic smartphone application.Objectives: The purpose of this study is to 1) determine Internet use patterns amongst orthopaedic patients; 2) ascertain access to and use of smartphones; and 3) elucidate what features orthopaedic patients find most important in a smartphone application.Methods: We surveyed patients in an orthopaedic practice in an urban academic center to assess demographics, access to and patterns of Internet and Smartphone use, and preferences for features in a smartphone app.Results: A total of 310 surveys were completed. Eighty percent of patients reported Internet access, and 62% used the Internet for health information. Seventy-seven percent owned smartphones, 45% used them for health information, and 28% owned health apps. Only 11% were referred to an app by a physician. The highest ranked features were appointment reminders, ability to view test results, communication with physicians, and discharge instructions. General orthopaedic information and pictures or videos explaining surgery were the 2 lowest ranked features. Seventy-one percent of patients felt an app with some of the described features would improve their healthcare experiences, and 40% would pay for the app.Conclusions: The smartphone is an under-utilized tool to enhance patient-physician communication, increase satisfaction, and improve quality of care. Patients were enthusiastic about app features that are often included in patient health portals, but ranked orthopaedic educational features lowest. Further study is required to elucidate how best to use orthopaedic apps as physician-directed educational opportunities to promote patient satisfaction and quality of care.Citation: Dattilo JR, Gittings DJ, Sloan M, Hardaker WM, Deasey MJ, Sheth NP. “Is There An App For That?“ Orthopaedic Patient Preferences For A Smartphone Application. Appl Clin Inform 2017; 8: 832–844 https://doi.org/10.4338/ACI-2017-04-RA-0058
Keywords: Smartphone; telemedicine; e-health; orthopaedic surgery; internet